The Effect of Internet Gaming Disorder on Learning Motivation of Students at Sman 21 Medan - Anisa, Andi; Akbar, Surya; Lestari, Ira Cinta; Darungan, Tezar Samekto (Jurnal Health Sains, 2025)
Online gaming behavior can increase excitement and reduce stress in students. However, uncontrolled online gaming behavior will lead to addiction which is then called Internet Gaming Disorder. Students with Internet Gamig Disorder tend to spend their time playing online games rather than their daily activities and this will have an impact on students' tasks as students by neglecting the levers so that they will lose their motivation to learn. This study aims to analyze the influence of Internet Gaming Disorder on the learning motivation of high school students. The design of this research is case control. The sample used in this study was 1:2 ratio, namely 27 students as case subjects and 54 students as control subjects. Data collection was carried out using IDGS-SF9 and AMS questionnaires. The results of this research data were analyzed using the Chi Square test. The results of the study found that the learning motivation of the case subjects was in the average category, namely 26 students (96.3%). Meanwhile, the control subjects of student learning motivation were relatively high, namely 34 students (63%). Based on the results of the Chi Square test, the influence of Internet Gaming Disorde on learning motivation (p<0.05) with an odd ratio of 44.2. Suggestions for further researchers could examine the influence of Internet Gaming Disorder on learning motivation in high school students with a larger population.